INTERSECTIONS OF FREEDOM, EXPRESSION OF CHRISTIAN FAITH AND CENSORSHIP IN TRANSLATED LITERARY WORKS: THE CASE OF HARRIET BEECHER STOWE’S NOVEL “UNCLE TOM’S CABIN” - Pranaitytė, Giedrė (Sustainable Multilingualism / Darnioji daugiakalbystė, 2025)
The connection between translation and censorship is one of the most inspiring subjects for the academic analysis that not only covers linguistic or cultural problems but sheds more light on important political issues as well. The current article focuses on the practical application of Soviet censorship techniques to the translation of Harriet Beecher Stowe’s novel “Uncle Tom’s Cabin” into Lithuanian. This canonical oeuvre of American literature was translated into the Lithuanian language and published in 1951. The aim of this article is to cast an attentive look at the theoretical considerations on the existing interconnection between the realms of translation and politics since these phenomena are seldom assessed in detail. After making an overview of different academic sources, it is possible to claim that Nicole Doerr’s (2018) basic premise on the prevalent existence of political translation is quite well-justified. The phenomenon of censorship, in turn, still happens to be sustained by the fear of authors and translators due to the potentially negative political evaluation of the dominant themes of certain literary works. The empirical part of the article is devoted to the examination of the Soviet censorship operating in practice in order to explain in what ways the translation of “Uncle Tom’s Cabin” into Lithuanian has failed to properly convey religious beliefs of the writer, which are closely linked to various fragments of the Bible. The hostility of the Soviet political elite towards essential Christian concepts was always systematic and consistent. However, the authentic practice of faith eventually turned into the essential obstacle to the political ambitions of the Communists to create a new Soviet man while diminishing the variety of existing attitudes and destroying the worldview based on religion.